Vulnerability to motor fuel price increases: Socio-spatial patterns in England. (June 2019) - Mattioli, Giulio; Philips, Ian; Anable, Jillian; Chatterton, Tim
Abstract: In high-motorisation, car-dependent countries, transport affordability is intimately linked to the price of oil derived motor fuels, which may become increasingly volatile in the future due to global oil price movements and environmental taxation. The negative impacts of fuel price spikes in terms of increased household expenditure and economic stress are unevenly spatially and socially distributed. Previous research has found that vulnerability to fuel price increases is higher in peripheral, peri-urban and rural areas, and that low income tends to be co-located with high car dependence and low vehicle fuel efficiency, with a compounding effect on vulnerability. The goal of this article is to test these hypotheses for England, providing new evidence on spatial patterns of vulnerability to fuel price increases at the small-area level. We propose a composite vulnerability indicator combining data on income, accessibility, vehicle inspection and vehicle registration for 2011. Within English city-regions, we find little evidence of the socially regressive patterns previously identified in the literature. This is explained by the persistent concentration of poverty in urban cores, as well as by the poor fuel economy of the vehicle fleet in wealthier areas, due to the prevalence of powerful vehicles there. On the other hand, our analysis suggests that the impacts of fuel price increases would be very unequal between city-regions, as the least sensitive metropolitan area (Greater London) is also characterised by high levels of adaptive capacity. We conclude by setting out an agenda for future research on spatial vulnerability to fuel price increases. Highlights: Vulnerability to fuel price increases is higher in the periurban North of England. Income and car dependence are positively correlated at small-area level in England. London is very resilient due to high income and low car dependence and expenditure. Vehicle fuel efficiency is inconsequential to spatial patterns of vulnerability. Oil vulnerability research must be sensitive to urban socio-spatial configurations.